Laboratory Validation of Mobile Sound Level Meter Applications Against Reference-Grade Instruments - Shree, Vidhya; Reddy, Venugopal (Journal of Research in Science and Engineering, 2026)
National Institute for Occupational Safety and Health (NIOSH) estimates that more than 22 million people in the United States are exposed to noise levels in excess of 85 A-weighted decibels (dBA) at their place of work. The World Health Organization (WHO) estimates that more than 5% of the work population (360 million people) have disabling hearing loss (WHO, 2012). Occupational noise-induced hearing loss is preventable. However, once acquired, it is permanent and irreversible (NIOSH, 1998). Advanced technology in the form smart phones have made everything accessible to its end users in the form of mobile application (apps). The smart phones work under two predominant platforms worldwide such as ANDROID and IOS. The sound level meter apps are available online for free. These apps can used to measure the noise level in the community and work place. This would help the public to identify noise levels by downloading free noise apps and be aware of the noise levels and take actions to conduct a comprehensive noise assessment and assess the need for reducing noise exposures and protect them from noise induced hearing loss and other non-auditory effects.